P14.60 FET PET response upon radiochemotherapy followed by Tumor Treating Fields (TTFields) in a patient with progressive high-grade glioma - Keßler, A F (Neuro Oncol, 2019)
BACKGROUND: The addition of Tumor Treating Fields (TTFields) to the first-line therapy in glioblastoma (GBM) demonstrated significantly improved progression free survival, overall survival and longterm survival rates in the EF-14 phase 3 trial. However, responder analysis of patients with recurrent GBM (rGBM) treated with TTFields monotherapy (in the EF-11 trial) revealed delayed response monitored by MRI analysis. More recent data suggests that O-(2-18F-fluoroethyl)-L-tyrosine (FET) PET may add valuable information for monitoring therapy response of glioblastoma patients treated with TTFields. Here, we report on FET PET response in a patient with progressive anaplastic astrocytoma WHO grade III (AA) treated with TTFields in combination with temozolomide (TMZ) chemotherapy. METHODS: We present a 38-year old patient with an initial diagnosis of a diffuse astrocytoma WHO grade II in 2011, and malignisation to an AA on progression. The treatment regimen included initially radio-chemotherapy (RCT) with TMZ. On further progression of the AA in 2017, TTFields were added to another 6 cycles of TMZ. Several FET PET scans for differentiation of tumor progression from treatment-related changes were performed over time. The definitive diagnosis (tumor progression and grading) was confirmed by histopathology after stereotactic biopsy (SB). RESULTS: In 2012, the patient was first diagnosed with a low grade astrocytoma WHO grade II of the right frontal, temporal and parietal lobe including infiltration of thalamus and corpus was confirmed by SB, followed by irradiation. On progression in 2015, a FET PET Scan showed FET avidity in all tumor affected regions of the brain. SB confirmed an AA, while FET PET scans showed only a mild response in the temporoparietal region after 6 cycles of TMZ. In 2017, the next progression without further malignisation was confirmed by SB and treated RCT with 41.4 Gy and TMZ chemotherapy, followed by application of TTFields with an average usage rate of 85.7 % over 6 months. Thus, the TTFields adherence was well above the independent prognostic threshold of 75 %. No additional adverse events due to the combined therapy of TTFields and TMZ were observed. Due to a new contrast enhancing lesion in the right frontal lobe (10x7mm), another FET PET scan was performed 1.5 years later. In this scan, obtained after combined TTFields and RCT therapy a strong response regarding FET avidity was observed. CONCLUSION: In summary, FET PET is able to add important additional information for evaluation of treatment response in high grade glioma patients, in particular for TTFields treated patients, while adding TTFields to radiochemotherapy might even enhance treatment response of high grade glioma. Further studies might elucidate the role of FET PET imaging for therapy monitoring in high grade glioma patients treated with TTFields.